Demographics and Outcomes of Patients With Eating Disorders Treated in Residential Care - Fisher, Martin; Henretty, Jennifer R.; Cox, Shelbi A.; Feinstein, Ronald; Fornari, Victor; Moskowitz, Lindsay; Schneider, Marcie; Levine, Sara; Malizio, Joan; Fishbein, Joanna (Frontiers in Psychology, 2020)
The use of residential eating disorder treatment has grown dramatically in the US, yet there has been minimal evaluation of treatment outcomes. Thus, outcome data on weight restoration, purging behaviors, and/or Global Assessment of Functioning (GAF) for 1,421 patients treated over an 8-year period in residential eating disorder programs are described. Results suggest that, 1) for patients who needed weight restoration upon admission, adolescent and adult patients gained 2.0 and 2.1lb/week, respectively; 2) of patients who reported purge behavior the month before admission, 89.1% were able to completely cease purging while in treatment; 3) although improvement of approximately 10 mean GAF points was made during treatment, patients were still quite impaired at discharge; 4) mean length of stay was 12 days longer for adolescents than adults, and 10 to 15 days longer for patients diagnosed with anorexia compared to bulimia or Eating Disorder Not Otherwise Specified (EDNOS), respectively. Other demographic statistics and additional analyses are presented. Limitations include the high variance of purging data and reliance on self- and parent-report for admission data. The data on the 1,421 patients, which represents 96% of all patients treated during the study period, more than doubles the number of residential eating disorder patients with outcome in the literature.